Metasurface-Integrated Flexible Antenna with Enhanced Bandwidth for Wearable IoT Devices - Sasank K.; Yuvaraju M.; Samantaray D.; Swain B.R.; Ram D.; Bhattacharyya S. (My University, 2025)
This paper describes a novel technique for wearable IoT applications that integrates the metasurface with flexible antenna. The antenna combines the functionalities of metasurface technology with the mechanical flexibility needed for wearable devices. The antenna comprises a 4×4 array metasurface and a rectangular patch utilizing U-shaped and circular slots on wool substrates. The design achieves a 3.29 GHz wide bandwidth (5.97 GHz- 9.26 GHz) and a 5.2 dBi realized gain. The enhanced bandwidth has been employed to improve data transmission and reception of the wearable devices. © 2023 IEEE.